Good practice report : English language proficiency. - Arkoudis, Sophie; Doughney, Lachlan (Australia. Office for Learning and Teaching, 2014)
This guide provides a summary of research into good practices in developing students' English Language Proficiency (ELP), and OLT/ALTC projects and fellowships associated with the issue. It also pinpoints gaps in the literature and makes recommendations for future work. The report offers insights into what works best in assuring that students graduate with the necessary communication skills for further study or employment. [Overview, ed]